Description of extreme longevity in the Balearic Islands: Exploring a potential Blue Zone in Menorca, Spain. Issue 3 (30th September 2013) - Soriano, Joan B; Fernández Vázquez, Sara; Carretero, Silvia; Puga González, María Dolores; Soriano, Cecilia; Romaguera, Dora; Alonso‐Fernández, Alberto; Busquets, Xavier; Balcells, Susana; Grinberg, Daniel; Poulain, Michel
<x xml:space="preserve">Abstract</x> Aim We aimed to determine whether there was a Blue Zone, an area characterized by extreme longevity, in Menorca, Spain. Methods We explored official statistics of the Balearic Islands, Spain, and calculated life expectancy from 1991 to 2009, by sex and island, among other demographic estimators. Results The life expectancy at birth in Menorca reached a peak in 2007 with 82.3 years, but since 2001 in females and 2007 in males, it plateaued and then descended. The percentage of centenarians in Es Migjorn Gran was 0.17% in 2001, only because of the 0.33% male contribution, and it returned to within the average Balearic rates. There is no record of any other surviving centenarian after 2006 in Es Migjorn Gran. Results obtained with other demographic indices are confirmatory. Conclusions It appears there was no extreme longevity or Blue Zone in Es Migjorn Gran and the surrounding villages in Menorca. Geriatr Gerontol Int 2014; 14: 620–627.